A randomized controlled trial to compare the success rates and efficacy of high flow nasal cannulae versus nasal continuous positive airway pressure in post extubation period in neonates - Awanti, Srinivas C.; Pol, Ramesh R.; Katti, Arun B. (International Journal of Contemporary Pediatrics, 2023)
Background: Nasal continuous positive airway pressure (nCPAP) is the mainstay for non-invasive respiratory support for all respiratory distress neonates. Recent advances in Heated humidified high flow nasal cannula (HHHFNC) usage with enhanced humidity, and improved comfort factors have led to its widespread use, at times replacing nCPAP in many neonatal settings. The present study was to assess the efficacy and safety of HHHFNC compared with nCPAP for non-invasive respiratory support in post-extubation period. Methods: A hospital based randomized controlled trial was conducted in neonatal intensive care unit (NICU) of S. Nijalingappa Medical College and HSK Hospital, Bagalkot from January 2019 to June 2020. 140 post-extubated neonates were enrolled for the study after obtaining informed consent from parents, and those who were directly extubated to no support and with major congenital anomalies were excluded from the study. Randomization was done by computer generated random number allocation method. Results: Of the140 babies, 60% were males and 40% were females. Out of 84 male neonates, 47 (67.1%) were on nCPAP and 37 (32.9%) on HHHFNC and out of 56 female neonates 23 (32.9%) were on nCPAP and 33 (47.1%) on HFNC. In this study, 4 babies on nCPAP required re-intubation within 72 hours. 5 babies on HHHFNC, 3 babies required re-intubation within 72 hours and 2 babies within 5 days. The incidence of nasal trauma, hospital stay and duration of NIV support were less in HHHFNC group as compared to nCPAP group. Conclusions: HHHFNC therapy is as effective as nCPAP therapy for the facilitation of extubation in neonates.